ChemInform Abstract: Cationic Iron(II) Complexes of the Mixed Cyclopentadienyl (Cp) and the N‐Heterocyclic Carbene (NHC) Ligands as Effective Precatalysts for the Hydrosilylation of Carbonyl Compounds. Issue 44 (4th November 2014) - Kumar, Dharmendra; Prakasham, A. P.; Bheeter, Linus Paulin; Sortais, Jean‐Baptiste; Gangwar, Manoj; Roisnel, Thierry; Kalita, Alok Ch; Darcel, Christophe; Ghosh, Prasenjit
Abstract The applied catalyst is prepared in moderate yield from the respective benzimidazolium iodide and CpFe(CO)2I.